Bathurst Inlet, Nunavut -- photograph - Seale, Linda N. (2001)
This former Hudson's Bay Company storehouse at Bathurst Inlet, Nunavut, was used by the Dominion Explorers company, making the first aerial survey of the (then) Northwest Territories in 1929. This is noted on a board above the door. Burnside River delta in the background. Photograph taken June 2001